(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the perception of dentists (DCs) from the private dental network of Patos de Minas about the treatments performed for non-carious cervical lesions (LCNCs). Due to the significant increase of LCNCs the different therapeutic conducts, identifying the most used parameters in the diagnosis and treatment of this condition, became necessary. The study is of applied nature, quantitative approach, with exploratory objective and field modality, with 62 DCs, who answered the questionnaire sent by obeying the current regulations. After data interpretation, the results were tabulated and analyzed descriptively. This study found that the DCs consider the multifactorial etiology of LCNCs, as well as the need to perform an occlusal evaluation. Moreover, the mechanical trauma of brushing may have an initiating and accelerating action, and it is essential that therapeutic decisions are based on parameters such as lesion depth and dentin hypersensitivity.